Recent Advances in Statistical Research in Forestry - Unnikrishnan, K. P.; Choubey, A.K. (Indian Forester, 1985)
Role of Statistics in the various facets of forestry research and management has been well recognised. This paper highlights some of the recent research work done on problems in forestry where statistical principles and methods have a larger role to play. They may be categorised as (i) studying of forest growth dynamics (ii) Nonparametric applications (iii) design of experiments and (iv) sampling. The applications of computer in forestry research is also highlighted in brief.